EFFECT OF OCCUPATIONAL HEALTH AND SAFETY AND SKILLS ON EMPLOYEE PERFORMANCE AT PT. LUTVINDO WIJAYA PERKASA PEKANBARU - onoadminmaster onoadminmaster (STIE Bangkinang Publishing, 2022)
The purpose of this study was to determine how the effect of occupational safety and health (K3) and skills affect the performance of employees at PT. Lutvindo Wijaya Perkasa pekanbaru. The analysis used is multiple linear. The number of samples in this study was 65 respondents. The sampling method uses the Slovin formula. Hypothesis testing is done by using the F test and t test. Based on the research results it can be concluded that simultaneously and partially. Occupational safety and health as well as skills affect employee performance. So it can be concluded that there is a very strong relationship between the independent variable and the dependent variable. This shows that the variables of occupational health and safety as well as skills as a whole have an effect of 69% on performance into the high influence category, while the remaining 31% is influenced by other variables not examined in this study.